UJI SIFAT FISIKOKIMIA SEDIAAN EKSTRAK DAUN ALPUKAT (Persea americana Mill.) DENGAN VARIASI KONSENTRASI ASAM STEARAT - Putri, Divia Tamara; Azzahra, Fara (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The content of avocado leaf extract such as polyphenol, saponins, alkaloids, tannins, quercetin and flavonoids can be made anti-acne cream preparations. This study aims to determine the physicochemical properties of avocado leaf extract cream including organoleptic tests, homogeneity tests, pH tests, and spread diameter tests. The research method used is experimental research with a posttest only design methodology. Avocado leaf extract is made in cream preparations using a stearic acid base, namely with variations in concentrations of F1(10%), F2(12.5%), and F3(15%). Data analysis used the oneway ANOVA test and the LSD test to determine the difference between variations in stearic acid concentrations in avocado leaf extract cream. The results of the research on organoleptic and homogeneity tests were carried out descriptively showed that F1 was light green, had a distinctive smell of avocado leaf extract, slightly thick, F2 was green color and F3 was brownish green, both of which have a distinctive odor of avocado leaf extract and are thick. Homogeneity shows the three formulas are not homogeneous. The pH test results were F1(7.85±0.05), F2(6.97±0.03) and F3(6.79±0.02) which had significant differences. The spread diameter results are F1(5.70±0.53cm), F2(5.56±0.35cm) and F3(5.36±0.31cm) have no significant differences. Organoleptic, pH and spread diameter tests meet the requirements whereas homogeneity tests do not meet the requirements. The factor of adding avocado leaf extract to the preparation and the unstable mixing speed, because it is done manually using a mortar and stamper, affects the homogeneity of the cream produced.